(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The ability for independent learning is increasingly recognized as a crucial skill for students in higher educational institutions. As educational systems evolve, fostering self-directed learning empowers students to take control of their academic journey and enhances lifelong learning capabilities. This paper explores the various aspects of developing independent learning among university students, focusing on key factors such as motivation, self-regulation, critical thinking, and access to resources. The study examines both the pedagogical strategies employed by educators and the intrinsic and extrinsic factors that influence students’ autonomy. The importance of cultivating a learning environment that encourages self-discipline, time management, and problem-solving skills is emphasized. Additionally, the role of digital tools and technologies in facilitating independent learning is discussed. The findings underscore the need for a holistic approach that integrates teaching methodologies, student support systems, and institutional policies to nurture this essential skill.